2019
DOI: 10.1038/s41374-018-0144-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-associated preventive effects of low-dose aspirin on obesity and non-alcoholic fatty liver disease in mouse offspring with over-nutrition in utero

Abstract: Aspirin has been found to diminish hypertriglyceridemia and hyperglycemia in both obese rodents and patients with type 2 diabetes mellitus. We aim to test if and how low dose aspirin is able to prevent obesity and the progression of non-alcoholic fatty liver disease (NAFLD) in the high risk subjects. We used offspring mice with maternal over-nutrition as a high risk model of obesity and NAFLD. The offspring were given postnatal HF-diet and diethylnitrosamine (DEN) to induce obesity and NAFLD, and were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…While, a large number of studies have also shown that the activation of AMPK signal pathway can reduce the deposition of lipid droplets and the occurrence of NAFLD. Zhou et al ( 42 ) found that a low dose of aspirin may reduce lipid droplet deposition via AMPK activation in the offspring of obese mothers. Devarajan et al ( 32 ) also reported that the occurrence of NAFLD in offspring with energy limitation during the perinatal period was related to AMPK changes.…”
Section: Discussionmentioning
confidence: 99%
“…While, a large number of studies have also shown that the activation of AMPK signal pathway can reduce the deposition of lipid droplets and the occurrence of NAFLD. Zhou et al ( 42 ) found that a low dose of aspirin may reduce lipid droplet deposition via AMPK activation in the offspring of obese mothers. Devarajan et al ( 32 ) also reported that the occurrence of NAFLD in offspring with energy limitation during the perinatal period was related to AMPK changes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the authors observed that aspirin reduced Wnt-signaling activity via hypo-methylation of the APC gene which explains its anti-proliferative effect interacting with beta-catenin only in female mice. 205 …”
Section: Discussion and Open Questionsmentioning
confidence: 99%
“…The administration of aspirin or acetaminophen was considered for the relief of the animals' pain. However, since there have been previous studies that showed that analgesics are effective in alleviating diseases in nonalcoholic fatty liver disease [13][14][15], this experiment was not used to confirm disease improvement through drug administration in liver disease animal models.…”
Section: Biopsy-proven Masld Model Using Pre-study Biopsymentioning
confidence: 99%